Сутність і зміст етапу закінчення досудового розслідування та їх значення для кримінальної процесуальної діяльності прокурора - Головко, Б. Ю.; Golovko, B. Yu. (Право і безпека. – 2017. – № 4 (67). – С.82-88, 2017)
Установлено, що сутність етапу закінчення досудового розслідування полягає у врегульованій КПК України діяльності учасників кримінального провадження, яка має значення для подальшого його перебігу внаслідок ухвалення підсумкового рішення, а зміст утворюється комплексом процесуальних дій організаційно-комунікативного характеру. Запропоновано виділити у структурі нагляду прокурора за додержанням законів під час проведення досудового розслідування окремий напрям – процесуальне керівництво прокурором закінченням досудового розслідування.

It has been proved that the conclusion of the pre-trial investigation, taking into account its legal nature as a part of the criminal proceedings, is expedient to consider, firstly, as a component of the criminal procedural activity at a certain stage of criminal proceedings; and secondly, as a set of criminal procedural norms that regulate the procedure of such activities; thirdly, as a part of the theory of criminal procedure, which provides the opportunity to work out the ways to improve the conclusion of the pre-trial investigation (activities and a set of norms). It has been established that the essence of this stage consists in the activity of the participants of criminal proceedings regulated by the Criminal Procedural Code of Ukraine, which matters for its further course as a result of adopting the final decision, and the content is formed by a complex of procedural actions of organizational and communicative nature. The structure of the form of the conclusion of the pre-trial investigation, which is the object of supervision by a prosecutor, has been defined as a set of legally significant facts and procedural actions that lead to the fulfillment of the tasks of this stage and the creation of preconditions for the fulfillment of the tasks of the criminal proceedings in general; its components include: 1) the conditions and grounds for the termination of the pre-trial investigation; 2) the state of execution of tasks at the stage of the conclusion of the pre-trial investigation; 3) compliance with the procedure of the conclusion of the pre-trial investigation; 4) ensuring the rights of participants in criminal proceedings involved in the final stage of the pre-trial investigation; 5) the content of the final procedural decision. Within the framework of the prosecutor’s supervision over the compliance with the laws during the conduction of the pre-trial investigation, it has been offered to allocate a separate direction – the prosecutor’s procedural guidance for the conclusion of the pre-trial investigation.

Установлено, что сущность этапа окончания досудебного расследования заключается в урегулированной УПК Украины деятельности участников уголовного производства, имеющей значение для дальнейшего его течения вследствие принятия итогового решения, а содержание образуется комплексом процессуальных действий организационно-коммуникативного характера. Предложено выделить в структуре надзорной деятельности прокурора за соблюдением законов при проведении досудебного расследования отдельное направление – процессуальное руководство прокурором окончанием досудебного расследования.
The essence and content of the stage of conclusion of the pre-trial investigation and their significance for the criminal procedural activity of a prosecutor
Сущность и содержание этапа окончания досудебного расследования и их значение для уголовной процессуальной деятельности прокурора
Головко, Б. Ю. Сутність і зміст етапу закінчення досудового розслідування та їх значення для кримінальної процесуальної діяльності прокурора / Б. Ю. Головко // Право і безпека. – 2017. – № 4 (67). – С.82-88.
Holovko, B.Yu. (2017), “The essence and content of the stage of conclusion of the pre-trial investigation and their significance for the criminal procedural activity of a prosecutor” [“Sutnist i zmist etapu zakinchennia dosudovoho rozsliduvannia ta yikh znachennia dlia kryminalnoi protsesualnoi diialnosti prokurora”], Pravo i Bezpeka, No. 4, pp. 82–88.
Keywords: Кримінально-процесуальне право. Criminal and Procedure Law. Уголовное процессуальное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; кримінальне провадження; кримінальна процесуальна діяльність; нагляд прокурора; прокурорський нагляд; процесуальне керівництво; досудове розслідування; закінчення досудового розслідування; уголовное производство; уголовная процессуальная деятельность; надзор прокурора; процессуальное руководство; досудебное расследование; criminal proceedings; criminal procedural activity; prosecutor’s supervision; procedural guidance; pre-trial investigation